Influence of exercise in normal and hot ambient conditions on the pharmacokinetics of inhaled terbutaline in trained men. (11th May 2016) - Kreiberg, M.; Becker, V.; Jessen, S.; Rzeppa, S.; Hemmersbach, P.; Backer, V.; Hostrup, M.
Abstract : This study investigated the pharmacokinetics of inhaled terbutaline at rest and after exercise in normal and hot ambient conditions with respect to doping analysis. Thirteen trained young men participated in the study. Urine and blood samples were collected after inhalation of 4 mg terbutaline during three trials: exercise in hot ambient conditions (30–35 °C) (EXH), exercise in normal ambient conditions (20–25 °C) (EX), and rest (20–25 °C) (R). Exercise consisted of 130 min at various intensities. Adjustment of urine concentrations of terbutaline to a specific gravity (USG) of 1.02 g/mL was compared with no adjustment. Area under the serum concentration–time curve within the first 6 h was higher for EX (27 ± 3 ng/mL/h) ( P ≤ 0.01) and EXH (25 ± 4 ng/mL/h) ( P ≤ 0.05) than for R (20 ± 3 ng/mL/h). When unadjusted for USG, urine concentrations of terbutaline after 4 h were different in the order EXH > EX > R ( P ≤ 0.01). When unadjusted for USG, urine concentrations of terbutaline were 299 ± 151 ng/mL higher ( P ≤ 0.001) after 4 h compared with adjusted concentrations in EXH. Excretion rate of terbutaline was higher ( P ≤ 0.001) for EX than for EXH and R within the first 0–1½ h. In conclusion, EXHs results in higher urine concentrations of terbutaline. This should be considered when evaluating doping cases of terbutaline.